2003
DOI: 10.1038/nn1084
|View full text |Cite
|
Sign up to set email alerts
|

The developmental origins of musicality

Abstract: The study of musical abilities and activities in infancy has the potential to shed light on musical biases or dispositions that are rooted in nature rather than nurture. The available evidence indicates that infants are sensitive to a number of sound features that are fundamental to music across cultures. Their discrimination of pitch and timing differences and their perception of equivalence classes are similar, in many respects, to those of listeners who have had many years of exposure to music. Whether thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
230
0
28

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(263 citation statements)
references
References 43 publications
5
230
0
28
Order By: Relevance
“…The notion of fostering musical appreciation in the infant is more difficult to locate in the literature and studies are more concerned with infant music perception skills (Ilari and Polka, 2006;Trehub, 2003) rather than establishing if prenatal exposure to music changes this relationship. Trehub (2003) for example, found that the music perception skills of infants as young as 6 months were well advanced and showed little difference to those of individuals who had many years of exposure to music. Infants recognised changes in tempo and pitch and demonstrated long-term memory of musical pieces.…”
Section: Facilitation Of Infant Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of fostering musical appreciation in the infant is more difficult to locate in the literature and studies are more concerned with infant music perception skills (Ilari and Polka, 2006;Trehub, 2003) rather than establishing if prenatal exposure to music changes this relationship. Trehub (2003) for example, found that the music perception skills of infants as young as 6 months were well advanced and showed little difference to those of individuals who had many years of exposure to music. Infants recognised changes in tempo and pitch and demonstrated long-term memory of musical pieces.…”
Section: Facilitation Of Infant Developmentmentioning
confidence: 99%
“…Infants recognised changes in tempo and pitch and demonstrated long-term memory of musical pieces. Although infants are clearly attracted to and responsive to maternal singing (Trehub and Nakata, 2001), it seems likely that this response may relate to social and emotional interaction (Trehub, 2003) as much as music appreciation.…”
Section: Facilitation Of Infant Developmentmentioning
confidence: 99%
“…One could waltz in time with a march, but the juxtaposition would be incongruous, because the gracefulness of waltz movements is sharply at odds with the rigidity and heaviness of march music (see Mitchell & Gallaher, 2001 and references therein for experimental support of these judgments). In our personal experience, even young children appreciate these differences in the character of music and improvise dances accordingly (see Trehub, 2003 on the sensitivity of very young children to musical affect). Similarly, orchestra conductors do not simply beat time: rather, their posture and the shape of their gestures convey the affective sense of the music.…”
Section: Affective Characteristics More Specific To Musicmentioning
confidence: 99%
“…To recognize a melody and move to (or perceive) the beat of music are trivial skills for most humans and, at the same time, fundamental to our musicality [20,34]. Even infants and young children are sensitive to a number of musical features that are common across cultures [35][36][37][38]. Although we are learning more and more about our own musical skills [39,40], the biological origins and evolutionary history of these apparent predispositions remain unclear.…”
Section: Biology and Culturementioning
confidence: 99%
“…Addressing these issues productively depends on distinguishing between the notions of music and musicality [28,31,35]. Musicality in all its complexity can be defined as a natural, spontaneously developing set of traits based on and constrained by our cognitive and biological system.…”
Section: Music and Musicalitymentioning
confidence: 99%